Long-Term Exposure to Ambient Air Pollution and Myocardial Infarction: A Systematic Review and Meta-Analysis - Zou, Li; Zong, Qiao; Fu, Wenning; Zhang, Zeyu; Xu, Hongbin; Yan, Shijiao; Mao, Jin; Zhang, Yan; Cao, Shiyi; Lv, Chuanzhu (Frontiers in Medicine, 2021)
Background and Objective: An increasing amount of epidemiological original studies suggested that long-term exposure to particulate matter (PM2.5 and PM10) could be associated with the risk of myocardial infarction(MI), but the results were inconsistent. We aimed to synthesized available cohort studies to identify the association between ambient air pollution (PM2.5 and PM10) and MI risk by a meta-analysis. Methods: PubMed and Embase were searched through September 2019 to identify studies that met predetermined inclusion criterion. Reference lists from retrieved articles were also reviewed. A random-effects model was used to calculate the pooled relative risk (RR) and 95% confidence intervals (CI). Results: Twenty-seven cohort studies involving 6,764,987 participants and 94,540 patients with MI were included in this systematic review. The pooled results showed that higher levels of ambient air pollution (PM2.5 and PM10) exposure were significantly associated with the risk of MI. The pooled relative ratio (RR) for each 10-μg/m3 increment in PM2.5 and PM10 were 1.18 (95% CI: 1.11–1.26), and1.03 (95% CI :1.00-1.05) respectively. Exclusion of any single study did not materially alter the combined risk estimate. Conclusions: Integrated evidence from cohort studies supports the hypothesis that long-term exposure to PM2.5 and PM10 as a risk factor for MI.